Species-specific mercury speciation in billfishes and its implications for food safety monitoring and dietary advice - Anaïs Médieu; David Point; Valérie Allain; Nathalie Bodin; Mélanie Lemire; Pierre Ayotte; Zahirah Dhurmeea; Matthieu Waeles; Laure Laffont; Antoine Le Gohalen; François Roupsard; Anne Lorrain (Environment International)
Humans are exposed to toxic methylmercury mainly by consuming marine fish, in particular top predator species like billfishes or tunas. In seafood risk assessments, mercury is assumed to be mostly present as organic methylmercury in predatory fishes; yet high percentages of inorganic mercury were recently reported in marlins, suggesting markedly different methylmercury metabolism across species. We quantified total mercury and methylmercury concentrations in muscle of four billfish species from the Indian and the Pacific oceans to address this knowledge gap. We found low percentages of methylmercury in blue and black marlins (15 ± 7 %) compared to swordfish and striped marlin (89 ± 13 %), with no significant differences among ocean regions. This illustrates that billfishes exhibit species-specific methylmercury bioaccumulation patterns, likely related to unique selenium-dependent in vivo methylmercury demethylation capacities in muscle. Blue and black marlins therefore appeared generally safer for human consumption than swordfish and striped marlin regarding MeHg toxicological effects. Yet, no matter the species, the frequency of recommended weekly billfish meals decreased with increasing fish size, given that mercury naturally accumulates over time. When assessing potential risks of billfish consumption, we therefore recommend measuring methylmercury, rather than total mercury, and relying on a large number of samples to cover a broad range of fish sizes. This study calls for additional characterization of mercury speciation and bioavailability in billfishes to better understand the mechanisms driving species-specific differences of methylmercury detoxification, and to refine dietary advices associated to marine top predators consumption.